Role of hypoxia-inducible factors in epigenetic regulation via histone demethylases. - Yang, J; Ledaki, I; Turley, H; Gatter, K; Montero, J; Li, J; Harris, A (2009)
Eukaryotic chromatin is subject to multiple posttranslational histone modifications such as acetylation, methylation, phosphorylation, and ubiquitination. These various covalent modifications have been proposed to constitute a "histone code," playing important roles in the establishment of global chromatin environments, transcription, DNA repair, and DNA replication. Among these modifications, histone methylation specifies regulatory marks that delineate transcriptionally active and inactive chromatin. These histone methyl marks were considered irreversible; however, recent identification of site-specific histone demethylases demonstrates that histone methylation is dynamically regulated, which may allow cells to rapidly change chromatin conformation to adapt to environmental stresses or intrinsic stimuli. Of major interest is the observation that these histone demethylase enzymes, which are in the Jumonji gene family, require oxygen to function and, in some cases, are induced by hypoxia in an HIFalpha-dependent manner. This provides a new mechanism for regulation of the response to hypoxia.